DNA-SIP and repeated isolation corroborate Variovorax as a key organism in maintaining the genetic memory for linuron biodegradation in an agricultural soil. Issue 5 (30th March 2021) - Lerner, Harry; Öztürk, Başak; Dohrmann, Anja B; Thomas, Joice; Marchal, Kathleen; De Mot, René; Dehaen, Wim; Tebbe, Christoph C; Springael, Dirk
ABSTRACT: The frequent exposure of agricultural soils to pesticides can lead to microbial adaptation, including the development of dedicated microbial populations that utilize the pesticide compound as a carbon and energy source. Soil from an agricultural field in Halen (Belgium) with a history of linuron exposure has been studied for its linuron-degrading bacterial populations at two time points over the past decade and Variovorax was appointed as a key linuron degrader. Like most studies on pesticide degradation, these studies relied on isolates that were retrieved through bias-prone enrichment procedures and therefore might not represent the in situ active pesticide-degrading populations. In this study, we revisited the Halen field and applied, in addition to enrichment-based isolation, DNA stable isotope probing (DNA-SIP), to identify in situ linuron-degrading bacteria in linuron-exposed soil microcosms. Linuron dissipation was unambiguously linked to Variovorax and its linuron catabolic genes and might involve the synergistic cooperation between two species. Additionally, two novel linuron-mineralizing Variovorax isolates were obtained with high 16S rRNA gene sequence similarity to strains isolated from the same field a decade earlier. The results confirm Variovorax as a prime in situ degrader of linuron in the studied agricultural field soil and corroborate the genus as key for maintaining the genetic memory of linuron degradation functionality in that field. Abstract : Variovorax is repeatedly identified as the key in situ linuron degrader in agricultural soil despite extended periods without pesticide application, suggesting its role in the maintenance of a genetic memory for linuron degradation.